Twenty-first century educational demands and interactive multimedia courseware evaluation criteria: educators' professional concerns - Samy, Chelvenderan Rama; Wong, Su Luan; Vethaman, Malachi Edwin; Abdul Samad, Arshad (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
With multimedia literacies as forefront challenges, operating in digital environments with multi-mode operatives and interactive multimedia heuristics pose to be newer challenges for educators in the 21st century. Multimedia challenges are shaping new instructional behaviours and learning paradigms. Multimedia literacies are now inevitable needs in a globalised world requiring more knowledge workers, with knowledge, skills, and values. Inevitably, educators are fitting into various roles in technology-rich environments as they face personal, social and professional changes in the new paradigm. Likewise, newer dimensions and paradigms evolving around English Language teaching in the 21st century are emerging. However, multimedia courseware evaluation criteria have somewhat remained static. Multimedia courseware evaluation criteria lack paradigms concerning pedagogy and classroom management issues, technical and instructional design concerns, value concerns, and gauging the effectiveness of multimedia courseware as instructional resources. This paper discusses these emerging professional concerns based on experiences gained from interactive multimedia courseware evaluation sessions.